The Labeling Effect of a Child Benefits System: Evidence from Russia 1994-2015 - Louise Grogan (Institute of Labor Economics (IZA), 2018)
Impacts of child benefits and earned incomes on child wellbeing are identified for Russia. To predict earnings, a counter-factual commodity price model is constructed using information on local industrial composition and the evolution of world prices during 1994-2015 for six key commodity exports. Discontinuity in benefits eligibility at age 16 is exploited to predict the probability of receipt. Child benefits are found not to be spent differently from earned incomes or to influence child health differentially. Benefits do not observably crowd out private transfers to households containing children. Earned incomes and child health appear to be little related.
Keywords: H3; I12; O12; O5; R11; 330; labour supply; Russia; child wellbeing; commodities prices; child benefits; program evaluation